The Influence of Public Service Handling Cases of Violence Against Women in: Collaborative Governance Perspective - RAJAK, Hadijah A.; SJAMSUDIN, Sjamsiar; SALEH, Choirul; WIKE, Wike (Journal of Tourism Economics and Policy, 2024)
This research aims to identify and analyze the service process in handling cases of violence against women in Tidore Islands City from a Collaborative Governance perspective. This research uses a mixed methods approach to analyze the model being analyzed. Research finds support for the model, and in particular for the central importance of active inclusion management. The research results show another source of data regarding the role of the Integrated Service Center for the Empowerment of Women and Children in the City of Tidore Islands in handling cases of violence against women. The research results show that P2TP2A Tidore Islands City focuses more on post-violence services through victim reports, but has not been effective in reducing the number of women's violence in the city. Therefore, preventive efforts are needed that increase public awareness of the dangers and negative impacts of violence against women. This research is limited to the context of Tidore City, and its findings may not be fully generalizable to other regions. This research underscores the importance of complete institutional design for the success of integrated services.